2015
DOI: 10.1111/jan.12706
|View full text |Cite
|
Sign up to set email alerts
|

Work‐to‐family conflict as a mediator of the relationship between job satisfaction and turnover intention

Abstract: Findings from this study indicate the importance of work-to-family conflict to nurse turnover. While work setting has a strong, well-documented influence on job satisfaction, limiting job satisfaction efforts to work setting improvements may not yield the hoped-for results unless work-to-family conflict is also considered and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 75 publications
10
72
0
11
Order By: Relevance
“…The vision provided by the participants is also consistent with what the literature reports regarding the dark side of the characteristics and tendencies of working conditions in general, both for their psychosocial risk factors 16 - 18 and because of the lack of wellbeing in health care work 5 - 7 , 10 - 12 , 26 - 27 , 30 - 31 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The vision provided by the participants is also consistent with what the literature reports regarding the dark side of the characteristics and tendencies of working conditions in general, both for their psychosocial risk factors 16 - 18 and because of the lack of wellbeing in health care work 5 - 7 , 10 - 12 , 26 - 27 , 30 - 31 .…”
Section: Discussionsupporting
confidence: 86%
“…These effects appear as a negative spiral of care pressure, staff shortage, task overload, time deficit to execute everything and to do so well, distress and burnout, absenteeism and presentism, rotation and abandonment of the workplace and profession 1 - 11 . The role of moderating variables in some of these effects, such as control of process and work content, horizontal and vertical social support, degree of adjustment between demands and labor resources, and the work-family balance or emotional load, has also been studied 12 - 15 . Some research reports the economic and human cost of the lack of prevention of psychosocial risks in work in general and particularly in health care services 16 - 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Amstad et al (2011) have shown that both WFC and FWC are positively correlated with turnover intention. Chen et al (2015) showed that among Taiwanese nurses, WFC mediates the relationship between job satisfaction and turnover intention to leave the present organization. In addition, one’s level of engagement is the key predictor of turnover intentions in Canadian registered nurses’ working at emergency departments (Sawatzky and Enns, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…A recent meta-analysis found that higher employee job satisfaction relates to higher customer satisfaction (Mendoza & Maldonado, 2014). Employees with more job satisfaction also perform better at work (Davar & Bala, 2012), have more organisational commitments (Magnini et al, 2011), less likelihood of turnover intention (Chen et al, 2015), and positively link to perceived organisational value (Edmans, 2012). Furthermore, higher job satisfaction is involved in lower work-to-family conflict (Chen et al, 2015), more subjective well-being like life satisfaction, happiness (Halkos & Bousinakis, 2010).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Employees with more job satisfaction also perform better at work (Davar & Bala, 2012), have more organisational commitments (Magnini et al, 2011), less likelihood of turnover intention (Chen et al, 2015), and positively link to perceived organisational value (Edmans, 2012). Furthermore, higher job satisfaction is involved in lower work-to-family conflict (Chen et al, 2015), more subjective well-being like life satisfaction, happiness (Halkos & Bousinakis, 2010). Hence, employees with higher job satisfaction will produce various benefits to their own performance as well as contributing to the organisation's performance.…”
Section: Job Satisfactionmentioning
confidence: 99%